New syllabus mathematics, workbook 1 (fifth edition) - Seng, Teh Keng; Yee, Loh Cheng Yeo, Joseph Chow, Ivy Har, Yeap Ban (Shinglee Publishers Singapore, 2007)
162-page student Level 1 workbook, incl. CD/ROM which includes templates to be used with some worksheets; book also includes Alternative Assessment worksheets section